Constraining forcing factors and relative sea‐level fluctuations in semi‐enclosed basins: the Late Neogene demise of Lake Pannon. (18th October 2014) - ter Borgh, M.; Radivojević, D.; Matenco, L.
Abstract: Sedimentary basins are affected by a large number of forcing factors during their evolution and as a result, it is often difficult to isolate the contribution of each individual factor. Many forcing factors are temporally and spatially heterogeneous; they do not affect all parts of the basin in the same way and at the same time. We show that this heterogeneity can be used to identify the contributions of forcing factors by comparing various parts of a basin. This approach is applied to the Pannonian Basin, a back‐arc basin located in Central Europe. In the basin, the amounts of crustal extension, tectonic inversion and sediment influx varied in space and time, while the connection with the marine realm fluctuated. In this study we focus on two currently unresolved issues: firstly, we establish by what processes and from what directions the basin was filled in, and secondly, we investigate whether the basin was affected by the Messinian Salinity Crisis. The analysis of seismic and well data in the previously less studied SE part of the basin demonstrate that progradation occurred from the southern and eastern basin margins, complementing the previously described progradation from the northwestern and northern basin margins. Elsewhere in the basin, an unconformity observed in the progradational basin infill is intensely debated to be the result of either the Messinian Salinity Crisis (MSC) or basin inversion. Having the advantage of minor Pliocene–Quaternary amounts of inversion in the studied part of the basin we show that no regional unconformity is present in the studied stratigraphic interval, which implies that the effects of the MSC on the basin were minor. We infer that being aware of the fact that the effects of relative sea/lake‐level fluctuations may vary significantly across a basin is critical for understanding the evolution of semi‐enclosed basins.